Gandhian Ideology of Republicanism in Chaman Nahal’s The Gandhi Quartetr - Kannadhaan, M. (International Journal of Psychosocial Rehabilitation, 2020)
Indian writing in English like all other new literatures of the world in English has been the outcome of national ferment and upsurge, which manifested itself as much in the socio-political life of the country. Of all the Indian writers who have used Gandhi for their creative purposes, Chaman Nahal is the most significant. His The Gandhi Quartet is a landmark in the annals of Indian English fiction which consists of the novels like The Crown and the Loincloth, The Salt of Life, The Triumph of the Tricolour and Azadi. The Gandhi Quartet successfully reconstructs the three stages of India’s struggle for freedom- the non-cooperation movement, the civil disobedience movement and the Quit India movement of 1942. It also gives a moving account of the division of India into India and Pakistan, and the disaster that follows it. In the end, Nahal seems to suggest that a return to Gandhi is the only solution to the problems people face today. It is hoped that a critical analysis of The Gandhi Quartet, the most expensive commonwealth novel, in terms of its themes and techniques, would help gain fresh insights into Nahal’s fictional art. Viewed in this context, acquires a greater significance, as it reminds us in unflinching terms, of the need to hold fast to the Gandhian ideals in a world torn apart by narrow sectarian and communal considerations.